1990
DOI: 10.1002/ss.37119905105
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on age differences

Abstract: The presence of adult learners on college campuses highlights the need to understand concepts of life span development, the process of revisiting psychosocial themes, and the nature of transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…A number of other personal attributes and strengths may also contribute to the selective nature of these and other nontraditional students. It is likely that individuals who decide to return to school later in life already possess a higher sense of self-efficacy, motivation, and commitment to educational goals (Higgins, 1985;Krager et al, 1990). Furthermore, when their academic achievement is high, as it was with this group, nontraditional students are likely to experience increased self-esteem, role gratification, and ego enhancement (Gerson, 1985;Kopp & Ruzicka, 1993;Leavitt, 1989;Padula, 1994) from taking on an unfamiliar role, in contrast to traditional students who have a more current and thus perhaps more fixed academic identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other personal attributes and strengths may also contribute to the selective nature of these and other nontraditional students. It is likely that individuals who decide to return to school later in life already possess a higher sense of self-efficacy, motivation, and commitment to educational goals (Higgins, 1985;Krager et al, 1990). Furthermore, when their academic achievement is high, as it was with this group, nontraditional students are likely to experience increased self-esteem, role gratification, and ego enhancement (Gerson, 1985;Kopp & Ruzicka, 1993;Leavitt, 1989;Padula, 1994) from taking on an unfamiliar role, in contrast to traditional students who have a more current and thus perhaps more fixed academic identity.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, the number of students entering postsecondary institutions immediately following high school has progressively decreased. Conversely, the registration of nontraditional students, defined as the "mature," "reentry," or "adult" learner over the age of 25, has substantially increased (Klein, 1990;Krager, Wrenn, & Hirt, 1990;Padula, 1994;Roehl & Okun, 1984;Scott, Burns, & Cooney, 1996). The majority of this group is female and is becoming the fastest growing population now entering postsecondary education (Clayton & Smith, 1987;Donaldson & Graham, 1999).…”
mentioning
confidence: 99%
“…Nonetheless, the literature points to several primary challenges that could be informative for those who have adult female students in their classroom or as their consultants and mentees, to better understand this particular group of students. Agar, 1990;Bauer & Mott, 1990;Bell, 2003;Benshoff & Lewis, 1992;Benshoff, 1992Benshoff, , 1993Chartrand, 1990;Compton, Cox, & Laanan, 2006;Crawford, 2004;Cross, 1980;Dill & Henley, 1998;Ely, 1997;Huston-Hoburg & Strange, 1986;Justice & Dornan, 2001;Kasworm, 2003;Kennedy, 2003;Klein, 1990;Krager, Wrenn, & Hirt, 1990;Lin & Wang, 2015;Lundberg, 2003;Mallinckrodt & Leong, 1992;McGivney, 2004;Muench, 1987;Puryear, 1988;Thon, 1984;Yarbrough & Schaffer, 1990) Studies of Female Adult Students (e.g., Anderson & Miezitis, 1999;Backels & Meashey, 1997;Carney-Crompton & Tan, 2002;Coker, 2003;Furst, 1991;Home, 1993Home, , 1997Jackman, 1999;Jacobs & King, 2002;King & Bauer, 1988;Kirk & Dorfman, 1983;Leavitt, 1989;Novak & Thacker, 1991;Padula, 1994;…”
Section: Findings From the Literature Reviewmentioning
confidence: 99%
“…They are often at least one-year away between high school and college (Dill & Henley, 1998). In addition, this population usually defined as over the age of 25 (e.g., Klein, 1990;Krager, Wrenn, & Hirt, 1990;Padula, 1994;Roehl & Okun, 1984;Scott, Burns, & Cooney, 1996). Early studies mentioned that from one-third to one-half of all college students are identified as nontraditional students and over 50% of all graduate students are over 30 years of age (Aslanian & Brickell, 1980;Elson, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Arguably the successful transition from school to higher education depends significantly on the integration of the student into the academic and social frameworks of an institution (Shobrook, 2003). Numerous studies have alleged that the speed and level of Higher education orientation units integration are greater the higher the level of an individual's "academic self-concept" (for details of relevant literature see, for example, Kreger and Wrenn, 1990;Michie et al, 2001;Bennett, 2004). A person with high academic self-concept inwardly feels that he or she is an "undergraduate type" who genuinely belongs at university (Van Overwalle, 1989).…”
Section: Academic Self-conceptmentioning
confidence: 99%